2013
DOI: 10.1163/15685411-00002709
|View full text |Cite
|
Sign up to set email alerts
|

A rapid in vitro bioassay system for testing resistance factors of pine trees to Bursaphelenchus xylophilus

Abstract: Understanding resistance mechanisms to pine wilt disease is essential to a successful breeding programme because plant selection cannot always guarantee absolute resistance against every isolate of the pine wood nematode, Bursaphelenchus xylophilus. To examine resistance factors in Japanese black pine, Pinus thwibergii, we devised a novel in vitro bioassay system in which we tested proliferation of pine wood nematodes co-cultured with wood slices or methanol extracts from pines. Proliferation of pine wood nema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As early as the 1990s, Yang Fujia advocated that research universities should take the initiative to communicate with top foreign universities; through such frequent cooperation, the universities in their own countries will benefit and rapidly improve their own standards. [3] Fudan University has made internationalization one of the university's development strategies, and is among the leaders in China in hosting international and regional academic conferences and in signing inter-university cooperation and exchange agreements with foreign universities. At the end of the Ninth Five-Year Plan (1996)(1997)(1998)(1999)(2000), there were more than 800 international students studying at Fudan Frontiers in Educational Research ISSN 2522-6398 Vol.…”
Section: Promoting Internationalization and Localization Of Universitiesmentioning
confidence: 99%
“…As early as the 1990s, Yang Fujia advocated that research universities should take the initiative to communicate with top foreign universities; through such frequent cooperation, the universities in their own countries will benefit and rapidly improve their own standards. [3] Fudan University has made internationalization one of the university's development strategies, and is among the leaders in China in hosting international and regional academic conferences and in signing inter-university cooperation and exchange agreements with foreign universities. At the end of the Ninth Five-Year Plan (1996)(1997)(1998)(1999)(2000), there were more than 800 international students studying at Fudan Frontiers in Educational Research ISSN 2522-6398 Vol.…”
Section: Promoting Internationalization and Localization Of Universitiesmentioning
confidence: 99%
“…In contrast, some reports indicated that bacteria might be endophytes which attach to the nematode cuticle, not taking part in PWD [7,10]. Although various control methods have been used to eradicate PWD, this disease has continued to expand over recent decades and has caused the destruction of hundreds of millions of pine trees, particularly in East Asia and southern Europe, which has resulted in enormous economic losses and profound ecological consequences [11][12][13][14][15][16][17]. In 1982, the disease was detected in pine forests in Nanjing, Jiangsu Province [18], and then has spread to 19 provinces and municipalities in 40 years [19].…”
Section: Introductionmentioning
confidence: 99%
“…Once an infection is established, most countermeasures for controlling the disease depend on chemical methods which are not economically effective. In comparison, breeding pine species for resistance to PWD is considered to be a fundamental strategy for prevention [12]. In southwestern Japan, breeding programs for pine species were initiated in 1978, mainly focusing on Pinus densiflora and Pinus thunbergii, and resistant plantations were successfully established in 1987 [21].…”
Section: Introductionmentioning
confidence: 99%